Assessing Accessibility Completeness in Public Open Spaces for People with Disabilities in Pokhara Metropolitan City, Nepal (Prithvi Academic Journal, 2025)
Public open spaces (POS) foster social interaction and enhance urban livability. However, these spaces often remain inaccessible to people with disabilities (PWDs), particularly wheelchair users and individuals with visual impairments. This study assesses the accessibility and suitability of POS in Pokhara Metropolitan City (PMC), focusing on identifying barriers and proposing improvements. Using a mixed-methods approach encompassing field observations, GIS mapping, and Focus Group Discussions (FGD), seven purposively selected POS were evaluated against key accessibility criteria. Findings reveal that while some POS accommodate wheelchair users, infrastructure for the visually impaired, such as tactile pavements, is entirely lacking. Uneven pathways, poorly designed restrooms, and inadequate signage further limit usability. The study highlights the need for comprehensive planning and policy reforms to promote inclusivity and universal design principles. Recommendations include installing physical pavements, improving restroom facilities, and involving PWDs in POS design processes. These efforts aim to create accessible and inclusive public spaces that enhance the quality of life for all.